Todos ligados na mesma emoção: o futebol e a cobertura das manifestações de 2013 e 2014 realizada pelo Jornal Nacional - Jéssica Montanhini de Souza (2019)
This present dissertation seeks to investigate the 2013 and 2014 Brazilian protests coverage made by Jornal Nacional, from Rede Globo Television Network. As the theoretical reference, it was resorted some authors such as Barbosa & Ribeiro (2005), Fortes (2011), Gruneau (1989), Asa Briggs (2012), amongst others. In order to carry out the research, the sources used were Jornal Nacional’s footage from the days that occurred Brazilian national team soccer matches in the 2013 Confederations Cup and in the 2014 World cup, provided by the online stream platform Globoplay. This research was based in a few methodological precepts from Bardin’s (1977) content analysis. It was possible to verify, after this study, among some other things, that the 2013 and 2014 protests were more multifaceted than what the Jornal Nacional meant to show on its coverage, with a lot of different claims and voices. It was also verified that the leisure and the media are intimately involved in what concerns commercial matters, such as sponsorships, audience, broadcast rights and dissemination.